Literasi Membaca Kritis Mahasiswa PGSD dalam Menganalisis Teks Bahasa Indonesia: Studi Mixed Method - Reni Guswita; Elfia Sukma; Syahrul Ramadhan (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
This study aims to describe the critical reading literacy profile of Elementary School Teacher Education (PGSD) students at Universitas Muhammadiyah Muara Bungo in analyzing Indonesian language texts, to identify influencing factors, and to explore the strategies and challenges they face. A mixed method research design with a sequential explanatory model was employed, integrating quantitative and qualitative approaches sequentially. Quantitative data were collected through a critical reading ability test and a literacy perception questionnaire administered to PGSD students. Qualitative data were obtained through in-depth interviews, classroom observations, and focus group discussions (FGDs) with selected students and Indonesian Language Skills course lecturers. The results indicate that the critical reading literacy of PGSD UMMUBA students falls in the moderate category (mean score 62.4%). Students demonstrate adequate competence in literal and inferential comprehension dimensions but remain weak in critical evaluation and ideological reflection of texts. Internal factors (motivation and reading habits) and external factors (teaching methods and availability of reading materials) significantly influence literacy achievement. The findings underscore the urgency of developing an integrated and systematic critical reading literacy curriculum in the PGSD program as a foundation for prospective elementary school teacher competence.